Reading the Historical Phenomenon of Australian Bushrangers - Yohanes Hartadi (Bina Nusantara University, 2009)
Outlaws in their various images have been important parts of history. In Australia, the longest lasting image of outlaws is the bushranger. Despite its popularity, there is a range of depictions of bushrangers and these are not necessarily similar. Interpretation of the bushrangers in colonial time differs from contemporary imagining. This papers aims at unfolding the various interpretations of the bushrangers in different periods in many types of artifact. Information was collected and interpreted by library research. The artifact analysis will be seen through a postmodernism theory by Michel Foucault and Roland Barthes. Since the phenomenon of bushranger stemmed from the colonial period, this study will commence from the period up to contemporary period. It can be concluded that a study of the different periods finds out that knowledge of the bushrangers does not make up a linear history, but rather a discontinuity in the historical narratives.